2012
DOI: 10.1038/eye.2012.84
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corpus geniculatum laterale and vitreous fluid by magnetic resonance spectroscopy in patients with glaucoma; a preliminary study

Abstract: Purpose To determine whether metabolite changes at cellular level occur in vitreous and lateral geniculate body (LGB) in patients with glaucoma by magnetic resonance spectroscopy (MRS). Methods A total of 29 eyes of 29 patients with glaucoma, no existing ocular pathology and systemic disease (group 1), and 13 eyes of 13 healthy individuals whose routine ophthalmological examinations were normal (group 2) were included in the study. Singlevoxel MRS examination was performed by placing region of interest in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
0
27
1
Order By: Relevance
“…Another study by Doganay et al [17] differs from our study with respect to the site of measurement. There were indeed differences in both technique and patient selection.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Another study by Doganay et al [17] differs from our study with respect to the site of measurement. There were indeed differences in both technique and patient selection.…”
Section: Discussioncontrasting
confidence: 69%
“…By contrast, Doganay et al studied single-voxel 1H-MRS on the LGB and corpus vitreous of 29 glaucoma patients and 13 healthy subjects [17]. They found statistically significant reduction of Glx/Cr ratio in both vitreous body and LGB, but no metabolite alteration in NAA/Cr and Cho/Cr ratios in the LGB.…”
Section: Introductionmentioning
confidence: 99%
“…MRS was performed using a VOI in these two regions in a group of glaucoma patients. Analysis revealed significantly greater levels of Glx:Cr in both VOIs for the glaucoma patients compared to sighted controls, supporting the apoptosis theory in the aetiopathogenesis of glaucoma . MRS could therefore move the diagnosis of glaucoma forward enhancing the understanding and diagnosing of glaucoma at the cellular level.…”
Section: Mrs In Visual Deficitsmentioning
confidence: 58%
“…In view of the apoptosis theory, in which the neurotoxicity of glutamate plays a pivotal role, a study was conducted with in vivo single-voxel NMR spectroscopy of the vitreous and lateral geniculate body of glaucoma patients. The authors found a higher glutamine-glutamate/Cr ratio in the vitreous and in the lateral geniculate body compared to healthy controls [10] . All of the study subjects were Caucasian, and hypertension, diabetes, and degenerative central nervous system diseases were excluded.…”
Section: Barbosa-breda Et Almentioning
confidence: 99%
“…In ophthalmology, metabolomics has been used to study various eye diseases including glaucoma [10][11][12][13][14][15][16] , age-related macular degeneration [17][18][19] , diabetic retinopathy [20][21][22] , keratoconus [23] , refractive error [24,25] , retinal detachment [26] , uveitis [27,28] , dry eye [29,30] , and other ocular surface diseases [31] . Analyses have been performed on tear fluid [23,[29][30][31][32] , aqueous humor [24,25,33,34] , vitreous humor [20,26,27,35,36] , cornea [37][38][39] , conjunctiva [40] , and lens [41,42] samples.…”
Section: Metabolomics In Ophthalmologymentioning
confidence: 99%